Teacher's pet ebook I can read level 1. - Cronin, Doreen (Diary of a Worm, 2013)
Worm is all about having fun, respecting the earth, and never taking baths. Many children will relate to this funny character! In Diary of a Worm: Teacher's Pet, Worm makes a surprising discovery—teachers have birthdays. That means Worm and his friends have to find the perfect present for their teacher, Mrs. Mulch. Diary of a Worm: Teacher's Pet is a Level One I Can Read book, which means it is perfect for kids learning to sound out words and sentences.